2018
DOI: 10.1098/rstb.2017.0136
|View full text |Cite
|
Sign up to set email alerts
|

Concrete versus abstract forms of social concept: an fMRI comparison of knowledge about people versus social terms

Abstract: The anterior temporal lobes (ATLs) play a key role in conceptual knowledge representation. The hub-and-spoke theory suggests that the contribution of the ATLs to semantic representation is (a) transmodal, i.e. integrating information from multiple sensorimotor and verbal modalities, and (b) pan-categorical, representing concepts from all categories. Another literature, however, suggests that this region's responses are modality- and category-selective; prominent examples include category selectivity for social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
121
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(139 citation statements)
references
References 128 publications
15
121
1
Order By: Relevance
“…The first part of this section presents two studies proposing new insights and methodological tools that reveal fine-grained differences between kinds of concepts [14,15]; the second part of the section includes papers that focus each on a specific kind of abstract concept (numbers [17], emotions [18,19], moral and aesthetic concepts [20], social concepts [16]). …”
Section: Kinds Of Abstract Conceptsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first part of this section presents two studies proposing new insights and methodological tools that reveal fine-grained differences between kinds of concepts [14,15]; the second part of the section includes papers that focus each on a specific kind of abstract concept (numbers [17], emotions [18,19], moral and aesthetic concepts [20], social concepts [16]). …”
Section: Kinds Of Abstract Conceptsmentioning
confidence: 99%
“…Rice, Hoffman, Binney and Lambon Ralph [16] use data of three neuroimaging studies comparing category-selective responses within the anterior temporal lobes (ATLs) to test the hub-and-spoke theory, which suggests that the ATL contribution to semantic representation is transmodal and concerns all categories. Rice et al compare the hub-andspoke theory with an alternative theory stating that this region's responses are modality-and category-selective, and respond specifically to socially relevant concepts including faces.…”
Section: Kinds Of Abstract Conceptsmentioning
confidence: 99%
“…We used a left ventral ATL site identified by Rice et al (2018b) as showing peak activation for semantic > non-semantic contrasts across eight studies using distortion-corrected fMRI (MNI coordinates -41, -15, -31). Since there is good evidence of bilateral engagement of ATL in semantic cognition, and Rice et al (2018b) identified a right ATL functional peak (MNI 44, -11, -36), we also included this seed in our investigation.…”
Section: Roi Selectionmentioning
confidence: 99%
“…difficulty when the task involves both social stimuli and picture inputs) or a wider problem with social concepts (Gainotti, 2013;Gorno-Tempini et al, 1998). A recent fMRI study (Rice et al, 2018b) directly compared the neural response in ATL during semantic decisions about specific entities that were social (people) and non-social (landmarks). The social and non-social stimuli were presented as both words (i.e., people's names) and as pictures (i.e., of faces).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation